Injectable Phosphorescence-based Oxygen Biosensors Identify Post Ischemic Reactive Hyperoxia - Jennifer S. Chien (Nature Portfolio, 2017)
Abstract Novel injectable biosensors were used to measure interstitial oxygenation before, during, and after transient ischemia. It is well known that reactive hyperemia occurs following a period of ischemia. However, increased blood flow does not necessarily mean increased oxygen tension in the tissue. Therefore, the purpose of this study was to test the hypothesis that tissue reactive hyperoxia occurs following release of hind-limb tourniquet occlusions. Rats were injected with bilateral hind-limb biosensors and were simultaneously subjected to a unilateral femoral vessel ligation. After approximately one and three months, the rats underwent a series of oxygenation challenges, including transient hind-limb tourniquet occlusion. Along with the biosensors, near infrared spectroscopy was used to measure percent oxyhemoglobin in capillaries and laser Doppler flowmetry was used to measure blood flow. Post-occlusion reactive hyperemia was observed. It was accompanied by tissue reactive hyperoxia, affirming that the post-occlusion oxygen supply must have exceeded the expected increased oxygen consumption. The measurement of the physiologic phenomenon of reactive hyperoxia could prove clinically beneficial for both diagnosis and optimizing therapy.